Comparison of Nalbuphine Hydrochloride and Fentanyl Citrate for Total Intravenous Anaesthesia in Short Surgical Procedures: A Randomised Control Study - Suman A Fefar; Rekha N Solanki; Jayshree M Thakkar; Shivratan Modi; Hiteshvari V Patel; Arunkumar Kethavath; Yarrie Vashi (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Total Intravenous Anaesthesia (TIVA) with propofol is gaining acceptance for day care surgeries due to its advantages over inhalational agents. Opioids administered as premedication are known to enhance the hypnotic effect of propofol and provide intraoperative and postoperative analgesia. Aim: To compare the effectiveness of Nalbuphine and Fentanyl for postoperative analgesia in short surgical procedures. Materials and Methods: In present double-blinded randomised controlled trail conducted in the Department of Anaesthesia at the Gujarat Cancer and Research Institute, Ahmedabad, Gujarat, India, 60 patients aged 18 to 60 years, classified as American Soceity of Anaesthesiologists (ASA) Grade-I or II, and scheduled for elective short surgical procedures under TIVA were randomly assigned to two groups. Group N received Nalbuphine 0.05 mg/kg, and control Group F received 0.001 mg/ kg Fentanyl intravenously before induction. Parameters studied included pain scores, first rescue analgesia, haemodynamics, and side effects. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS Inc., Chicago, IL, USA, version 19.0 for Windows). Parametric data were analysed using paired and unpaired t-tests. Results: Data from a total of 60 patients (Group N mean age: 46.9±9.96 years and Group F mean age: 46.6±10.44 years) were collected and analysed. Both groups were comparable in terms of age, Body Mass Index (BMI), mean duration of surgery, and type of surgery (p > 0.05). Pain scores on the Visual Analogue Scale (VAS) were not significant upto 15 minutes after surgery, but thereafter, the VAS score was significantly lower in the Nalbuphine group (p-value < 0.05). Intraoperative episodes of significant hypotension were observed only in the Fentanyl group (p-value < 0.05). The total dose of propofol required was significantly lower in the Fentanyl group (p-value < 0.001). The time to the first rescue analgesia requirement (in minutes) was significantly shorter in the Fentanyl group (32.83±28.43) compared to the Nalbuphine group (56.37±25.31). Side effects such as postoperative sedation, nausea, and vomiting were observed in the Fentanyl group (p-value >0.05). Conclusion: Nalbuphine provided superior postoperative analgesic effects compared to Fentanyl when used as an analgesic component in TIVA. Postoperatively, pain scores were lower, and the time to the first rescue analgesia was longer in the Nalbuphine group.